ANALISIS KOMPOSISI DIATOM EPIPELIK SEBAGAI BIOINDIKATOR PENCEMARAN PERAIRAN PANTAI KOTA DUMAI PROVINSI RIAU - Zahrotul Aini; Aras Mulyadi; Bintal Amin (Lembaga penelitian dan pengabdian kepada masyrakat, 2017)
This study was conducted in August 2014 with a survey method. Five sampling stations was chosen by taking into account differences in the surrounding anthropogenic activities. Sampling for epipelic diatoms in sediment was performed by using spatula on 5x5 cm subplots in sediment samples taken by ekman grab. Water quality parameters measured at each station are the current speed, temperature, salinity, pH, BOD, nitrate, phosphate, organic matter and sediment fractions. The results of the study found as many as 16 species of epipelic diatoms. Melosira sp., Navicula sp. and Nitzshia sp. are the dominant species and the possibilities to be considered as an indicator for water pollution status of Dumai coastal waters. Average abundance of epipelic diatoms ranged between 18.67 ind/cm2 to 67.33 ind/cm2. Epipelic diatom diversity index ranged from 1.667 to 1.960; the dominance index ranged from 0,288 to 0,392 while theuniformityindexranged from 0,891 to 0,951. The level of water pollution based on the diversity index indicated that Dumai coastal waters is catagorized as low to moderately polluted waters